Effect of Repeated Remote Ischemic Preconditioning on Peripheral Arterial Disease in Patients Suffering from Intermittent Claudication - Balin, Mehmet; Kivrak, Tarik (Wiley, 2019)
Background/Objective. Intermittent claudication (IC) is the symptom of peripheral artery disease (PAD) and causes functional disability. Remote ischemic preconditioning (RIPC), is a phenomenon in which a short period of sub-critical ischemia, protects tissues against ischemia/reperfusion/injury. We considered to test the hypothesis that RIPC in PAD patients suffering from IC would increase muscle resistance to ischemia and thus improve walking-capacity. Materials/Methods. A total of 63 patients with proven-IC underwent two treadmill tests (graded treadmill protocol) with a 28-day interval in between. Patients were consecutively assigned for the non/RIPC-group and RIPC-group procedure one by one. Patients received 5-cycles of alternating 5-minute inflation and 5-minute deflation of blood-pressure cuffs on nondominant upper-limb every day for four weeks. Initial claudication distance (ICD), total walking distance (TWD) and time to relief of claudication (TRC) were recorded during procedure. Results. Patients receiving-RIPC exhibited a marked increase in ICD and TWD between basal and last tests: 209.1 +/- 15.4 m vs. 226 +/- 15.0 m and 368.8 +/- 21.0 m vs. 394 +/- 19.9 m, respectively (p<0.001). In addition, patients receiving-RIPC represented a significant decrease in TRC between basal and last tests: 7.8 +/- 1.3 min vs. 6.4 +/- 1.1 min, respectively (p<0.001). Patients not receiving-RIPC did not exhibit improvement in ICD, TWD, and TRC between basal and last tests: 205.2 +/- 12.1 min vs. 207.4 +/- 9.9 min, 366.5 +/- 24.2 min vs. 369.4 +/- 23.2 min and 7.9 +/- 1.4 min vs. 7.7 +/- 1.3 min, respectively (p>0.05). Conclusion. A significant increase in ICD and TWD were observed in last/treadmill test in RIPC-group. In addition, a significant decrease in TRC was observed in last/treadmill test in RIPC-group. In non/RIPC-group, no improvement was observed in ICD, TWD and TRC.
Keywords: Ankle Brachial Index; Lower-Extremity; Task-Force; Cardioprotection; Guidelines; Society; Humans; Injury